Analisis Pengaruh Ukuran Serbuk Kaca Pada Pembuatan Kanvas Rem Sepeda Motor Dengan Pengisi Serbuk Piston Bekas - Anggria, Feldy; Nawangsari, Putri; Masnur, Dedy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Waste glass and piston can be used as alternative material to non-asbestos brake pads with powder metallurgy method. Waste glass was used as a reinforce, the piston was used as a filler, and phenolic resin was used as a binder. This study purposes to investigates the influence of size the glass powder particles on the wear resistance and hardness. The powders composition of phenolic resin, piston, and glass was 40%, 40% and 20% respectively, based on volume fraction. The glass powder was mixed in three varied sizes which is 60, 80, and 100 mesh. The mixing process was conducted in 30 minutes mixing time at 45 rpm. 166 bar preliminary pressure was applied at the beginning of single action compacting for 2 minutes then 196 bar and in single action hot compacting at 150°C for 5 minutes, then it was sintered at 150°C for 4 hours. Then, the samples were followed hardness test and wear test. The results showed the composition of the 60 mesh glass has the closest hardness and wear value to the commercial product which is 41.296 HVN and 8.2795 x 10-12 m3/m.Keyword : Brake pads, Waste glass, Particle size